Two new species of Diaptomidae (Crustacea: Copepoda: Calanoida) from the Neotropical Region (Paraná River) - Perbiche-Neves, Gilmar [UNESP]; Boxshall, Geoff A.; Paggi, Juan C.; da Rocha, Carlos E.F.; Previattelli, Daniel; Nogueira, Marcos G. [UNESP] (Taylor & Francis, 2013)
Two new species of Diaptomidae were found in the Middle Paraná River. The new species are referred to as Diaptomus curvatus sp. nov. and Diaptomus frutosae sp. nov. Important character states in Diaptomus curvatus include: right fifth leg with a well-developed endopod and with the lateral spine of the second exopod segment curved and longer than the segment on which it is inserted, plus the presence of a large dorsal process on urosomite 4 of the male. For Diaptomus frutosae they include: a differentiated hook-like process on segment 20 with chitinous protuberances at base of male right antennule; the last segment of the right leg 5 of male is triangular, and the lateral spine inserted distal to mid-level of this segment. Both species are placed in Diaptomus sensu lato as a temporary placement. http://www.zoobank.org/urn:lsid:zoobank.org:pub:FECDD6C4-C0AC-4043-ADDD-F29539B451F0. © 2013 Copyright Taylor and Francis Group, LLC.
Keywords: Argentina; Copepoda; new species; Paraguay; anatomy; biological characteristics; crustacean; Neotropical Region; Parana River; Calanoida; Crustacea; Diaptomidae; Diaptomus